Are we ready for a sustainable approach? A qualitative study of the readiness of the public health system to provide STI services to the key populations at risk of HIV in Bangladesh - Gorkey Gourab; Golam Sarwar; Mohammad Niaz Morshed Khan; A M Rumayan Hasan; Samira Dishti Irfan; Tarit Kumar Saha; Lima Rahman; A. K. M. Masud Rana; Sharful Islam Khan (BMC Health Services Research, 2023)
Abstract Introduction In Bangladesh, sexually transmitted infection (STI) services are available for all populations in public health facilities. However, STI services for key populations (KPs) at risk of HIV need specifically designed approaches that are predominantly administered to KPs through donor-supported service centers operated by non-government organizations (NGOs) and community-based organisations (CBOs). However, the steady decline in donor funding warrants a sustainable transition of STI services for the KPs into public health facilities. This article aimed to explore the service availability and readiness of public health facilities to provide STI services for the KPs. Methods This qualitative study explored the service availability and readiness of public health facilities in three districts of Bangladesh by adapting the Service Availability and Readiness Assessment tool. We conducted 34 in-depth interviews,11 focus group discussions with KPs, and 29 key-informant interviews with healthcare providers, researchers, programme implementers and policy planners, in addition to series of direct observations at the public healthcare facilities. Data were analysed through thematic analysis, and categorised in relation to the WHO building blocks. Results This study revealed that the public health system was generally not ready to serve the KPs’ needs in terms of providing them with quality STI services. The ‘service delivery’ component, which is the most crucial facet of the public health system, was not ready to provide STI services to KPs. Findings also indicated that health workforce availability was limited in the primary and secondary healthcare layers but adequate in the tertiary layer, but needed to be oriented on providing culturally sensitised treatment. Counseling, an essential component of STI services, was neither ready nor available. However, health information systems and a few other components were partially ready, although this warrants systematic approaches to address these challenges. Conclusion The findings show that public health facilities are yet to be fully ready to render STI services to KPs, especially in terms of service delivery and human and health resources. Therefore, it is not only integral to mobilize communities towards the uptake of public health services, but health systems need to be prepared to cater to their needs.